The more the better?: foreign ownership and corporate performance in China - Yu, Zhihong; Greenaway, David; Guariglia, Alessandra (Taylor & Francis, 2014)
We examine the relationship between the degree of foreign ownership and performance of recipient firms, using a panel of 21,582 Chinese firms over the period 2000–2005. We find that joint-ventures perform better than wholly foreign-owned and purely domestic firms. Although productivity and profitability initially rise with foreign ownership, they start declining once it reaches a certain point. This suggests that some domestic ownership is necessary to ensure optimal performance. We referred these findings to a model of a joint-venture, where strategic interactions between a foreign and a domestic owner's inputs may lead to an inverted U-shaped ownership–performance relationship.